Glucose-6-Phosphate Dehydrogenase (G6PD) status in Female Type 2 Diabetes Mellitus and its Relationship with HbA1C - Akter, Nadira; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2011)
Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency may be one of the risk factor for type 2 diabetes mellitus. Objective: To observe erythrocyte G6PD status in type 2 female diabetic patients and also to find out its relationship with glycosylated hemoglobin. Methods: This cross sectional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka from January to December 2009. For this, 60 female patients with type 2 diabetes mellitus, age ranged from 40 to 60 years were included in the study group (group B). On the basis of glycosylated hemoglobin level (HbA1C) they were further subdivided into group B1, consisting of 30 controlled diabetics (HbA1C 4.8-6%) and group B2, consisting of 30 uncontrolled diabetic (HbA1C>6%) patients. They were selected from Out Patient Department of Bangladesh Institute of Health Science Hospital. For comparison, age & sex matched 30 apparently healthy non diabetic females (group A) were also studied. Erythrocyte G6PD level was measured by Spectrophotometer, HbA1C level by Flex reagent cartridge and serum bilirubin, Hb%, total count of RBC and reticulocyte% were measured by standard laboratory techniques. For statistical analysis ANOVA, independent sample t test, χ2 test and Pearson's correlation coefficient test were performed as applicable. Results: In this study, erythrocyte G6PD level was significantly lower in both the diabetic groups (p <0.001) than those of control group but their difference when compared between B1 and B2 was not statistically significant. In controlled diabetics 20% and in uncontrolled diabetics 6.7% patients were found G6PD deficients. No G6PD deficient subjects were found in control group. HbA1C showed negative correlation with Erythrocyte G6PD which was only significant for uncontrolled diabetes (p < 0.05) Conclusion: This study concludes that G6PD deficiency may be one of the risk factor for type 2 diabetes mellitus irrespective of blood glucose control status. Key words: Glucose-6-PD; Diabetes; Female. DOI: 10.3329/jbsp.v5i2.6778 J Bangladesh Soc Physiol. 2010 December; 5(2): 60-65